Electroacupuncture-Induced Neuroprotection against Cerebral Ischemia in Rats: Role of the Dopamine D2 Receptor. (21st November 2013) - Xu, Ming-Shu; Zhang, Shu-Jing; Zhao, Dan; Liu, Cheng-Yong; Li, Chang-Zhi; Chen, Chun-Yan; Li, Li-Hui; Li, Ming-Zhe; Xu, Jia; Ge, Lin-Bao
Abstract : Background . Cerebral ischemia is known to produce brain damage and related behavioural deficits, including memory deficits and motor disorders. Evidence shows that EA significantly promotes recovery of neurological function and thus improves quality of life. Objective . Evidence exists for the involvement of catecholamines in human neuroplasticity. A better understanding of dopaminergic (DAergic) modulation in this process will be important. Methods . A total of 72 adult male Sprague-Dawley (SD) rats were divided into 6 groups: normal, model, EA, spiperone group, EA + spiperone group, and pergolide. The middle cerebral artery occlusion (MCAO) model was used in all 6 groups except the normal group. A behavioural assessment was conducted at 1, 3, 5, and 7 days after MCAO. The percent of brain infarct area was also determined 7 days after MCAO. Tyrosine hydroxylase (TH) and growth-associated protein 43 (GAP-43) fluorescence double labeling was performed in the striatum. Results . In this study, we found that EA at Fengchi (GB20) acupoints resulted in marked improvements based on a behavioural assessment. Both TTC staining and GAP-43 immunofluorescence labeling results showed that EA treatment reduced ischemia injury and promoted neuroplasticity compared with the model group. The D2R-selective agonist, pergolide, showed similar results, but these results were reversed by the D2R-selective antagonist, spiperone. We also found that there were more colocalization and expression of GAP-43 and TH in the EA and pergolide groups than those in the other groups. Conclusion . These results suggest that the neuroplasticity induced by EA was mediated by D2 autoreceptors in DAergic neurons.